Anapulvinaria pistaciae (Bod.), a pistachio tree scale pest producing honeydew foraged by bees in Greece - Santas, L.A. (ENTOMOLOGIA HELLENICA, 1985)
The soft scale Anapulvinaria pistaciae (Bod.), a pest of pistachio, excretes honeydew which is exploited by honeybees. The scale has one generation per year. Adults appear early in spring and crawlers in May. From mid-May to mid-June the population of A. pistaciae consists mainly of crawlers and/or first stage nymphs. The second stage nymphs appear early in fall, this is the over-wintering stage, from which the adults of the next generation will emerge the following year.